1980
DOI: 10.1111/j.1600-0447.1980.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTH4–10 and memory in ECT‐treated patients and untreated controls II. EFFECT ON RETRIEVAL

Abstract: The aim of the investigation was to find whether a single dose of ACTH4-10 could alleviate the retrograde dysmnesic effects of unilateral ECT and improve retrieval. Twenty depressive inpatients participated in the study, which was a double-blind intraindividual cross-over comparison between ACTH4-10 (30 mg subcutaneously) and placebo. The drug was administered 150 min after learning and 90 min after the second or third ECT unilateral treatment. Retrieval was tested 30 min after the administration of the drug. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“… 57 Two studies, one crossover trial 58 and one non‐randomized trial, 59 found no evidence of effect of anticholinergic agents on immediate cognitive outcome. Three crossover trials 60 , 61 , 62 and one trial supplying insufficient data for quantitative synthesis 62 found no effect of pharmacological interventions targeting the cortisol pathway. One crossover trial (n = 15) did not detect an effect of myo‐inositol.…”
Section: Resultsmentioning
confidence: 99%
“… 57 Two studies, one crossover trial 58 and one non‐randomized trial, 59 found no evidence of effect of anticholinergic agents on immediate cognitive outcome. Three crossover trials 60 , 61 , 62 and one trial supplying insufficient data for quantitative synthesis 62 found no effect of pharmacological interventions targeting the cortisol pathway. One crossover trial (n = 15) did not detect an effect of myo‐inositol.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ] Adrenocorticotropic hormone was found ineffective in immediate recall, memory retrieval, or consolidation of memory. [ 27 28 29 ] A double-blind study on cytidine-5′-diphosphocholine-choline did not show any protection against ECT-induced memory dysfunction. [ 30 ] Adjunctive T3 hormone showed better memory function in patient receiving ECT in a double-blind placebo controlled study.…”
mentioning
confidence: 99%